Characteristics of Patients With Chronic Hepatitis B Virus Infection With Genotype E Predominance in Burkina Faso. Issue 12 (15th September 2020) - Wongjarupong, Nicha; Yonli, Albert Theophane; Nagalo, Bolni Marius; Djigma, Florencia Wendkuuni; Somda, Sosthene Kounpielime; Hassan, Mohamed A.; Mohamed, Essa A.; Sorgho, Abel Pegdwende; Compaore, Tegwinde Rebeca; Soubeiga, Serge Theophile; Kiendrebeogo, Isabelle; Sanou, Mahamoudou; et al.
Abstract : Hepatitis B virus (HBV) genotype E (HBV‐E) accounts for the majority of chronic hepatitis B (CHB) infections in West Africa. We aimed to determine factors associated with HBV‐E‐induced hepatocellular carcinoma (HCC) in West Africa. Data on patients from Burkina Faso who were hepatitis B surface antigen positive (HBsAg+) and had CHB were analyzed. HBV viral load and hepatitis B e antigen (HBeAg) status were measured in 3, 885 individuals with CHB without HCC (CHB HCC−) and 59 individuals with CHB with HCC (CHB HCC+). HBV genotyping was performed for 364 subjects with CHB HCC− and 41 subjects with CHB HCC+. Overall, 2.5% of the CHB HCC− group was HBeAg+ compared with 0% of the CHB HCC+ group. Of the 364 patients who were CHB HCC− with available genotyping, the frequencies of HBV genotypes E and C/E were 70.3% and 12.9%, respectively. Age (odds ratio [OR] for older age, 1.08; 95% confidence interval [CI], 1.06‐1.10 per 1‐year increase in age), male sex (OR, 2.03; 95% CI, 1.11‐3.69), and HBV viremia (OR, 1.48; 95% CI, 1.31‐1.67 per 1 log10 IU/mL) were each associated with HCC diagnosis. Patients with genotype E had a lower HBeAg prevalence (6.3% vs. 14.9%), lower HBV viral load, and higher prevalence of cirrhosis (14.5% vs. 4.8%) than patients with genotype C/E. Conclusion: HBV‐E is the most common circulating strain (70.3%) in West African patients. HCC was associated with older age, male sex, and high HBV viral load. It is expected that these results will further inform guidance on clinical management of HBV infection in West Africa. Abstract :